Tailored to Women, Provided to Men? Gendered Occupational Inequality in Access to Flexible Working-Time Arrangements - Aljoscha Jacobi; Maik Hamjediers; Tabea Naujoks (Social Indicators Research, 2024)
Numerous policy-makers and social scientists promote flexible working as a means to reconcile work and family life, often explicitly targeting women. Accordingly, one might expect that flexible working-time arrangements are more prevalent in occupations with a high share of female employees. Yet, previous evidence indicates the opposite. To address this puzzle, we investigate the occupational opportunity structures for flexible working. A devaluation argument proposes that employers perceive female-typed work as being of lower value, thus inhibiting the provision of flexible working-time arrangements in tfemale-dominated~occupations. We evaluate this argument against alternative explanations, namely differences in the ability to bargain for flexible working and in structural or practical barriers to flexible working. Descriptive results based on German panel data (GSOEP, 2003–2017) enriched with occupational-level information confirm that female-dominated occupations provide the least access to flexible work. Linear probability models with yearly fixed-effects indicate that power resources and structural barriers account for differences in flexible working between male-dominated and integrated occupations; yet an unexplained disadvantage for female-dominated occupations remains. Moreover, this disadvantage has grown between 2003 and 2017. We interpret this result as support of a cultural devaluation of female-dominated occupations in access to flexible working-time arrangements. Our findings highlight that the empirical reality of gendered occupational opportunity structures contradicts the gendered policy discourse on flexible work.
Keywords: 300; Flexible working; Gender; Occupational gender segregation; Devaluation; Germany